Dialectics of rights and responsibilities in education - Pokhylenko, I; Davydova, N; Mialovytska, N; Zlatina, N; Otradnova, O (My University, 2022)
The objective of the article was to analyze the dialectic of rights and responsibilities in education. The importance of education is so great that the thesis of the responsibility of the person to receive education has now been recognized. In order for the right to education to be exercised, the domestic law of states provides for a set of responsibilities for participants in the educational process, the implementation of which actually guarantees access to education. The real economic opportunities of States have a great impact on the real content of the dialectical process of interaction of rights and responsibilities in the field of education. The relationship between the participants in the educational process is regulated at several levels: first, the rules of domestic law and then the contractual level, represented by the statutes of educational institutions, comes into force. It is concluded that, in the most advanced systems, there may be a level of intra-group agreements that are completely voluntary. The practical content of the educational process is influenced by several factors, including ideology, the objectives set by a given society, tThe objective of the article was to analyze the dialectic of rights and responsibilities in education. The importance of education is so great that the thesis of the responsibility of the person to receive education has now been recognized. In order for the right to education to be exercised, the domestic law of states provides for a set of responsibilities for participants in the educational process, the implementation of which actually guarantees access to education. The real economic opportunities of States have a great impact on the real content of the dialectical process of interaction of rights and responsibilities in the field of education. The relationship between the participants in the educational process is regulated at several levels: first, the rules of domestic law and then the contractual level, represented by the statutes of educational institutions, comes into force. It is concluded that, in the most advanced systems, there may be a level of intra-group agreements that are completely voluntary. The practical content of the educational process is influenced by several factors, including ideology, the objectives set by a given societyhe traditions and customs that have developed in it.
Dialéctica de derechos y responsabilidades en la educación
Keywords: educational process; legislation; actual content of rights and responsibilities; education law; dialectic of rights educational process